1990
DOI: 10.1111/j.1365-2494.1990.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Sward composition, animal performance and the potential production of grass/white clover swards continuously stocked with sheep

Abstract: The poteniia] productivity of perennial ryegrass/ white clover swards (GC) under continuous stocking management was assessed by comparing their performance, when grazed by sheep at sward surface heights of 3, 6 and 9 cm, with that of an all-grass sward (G) maintained at 6 cm and fertilized with 420 kg N ha " '. The grass/ clover swards received no nitrogen fertilizer. The different grazing treatments had a marked effect on animal performance. In the first year for example, for treatments GC3, GC6, GC9 and G6-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
5
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 17 publications
10
71
5
3
Order By: Relevance
“…Pesquisadores (Orr et al, 1990;Penning et al, 1991;Armstrong, 1995) verificaram que as maiores produções por área ocorreram em menores alturas da pastagem, porém com reduzido desempenho animal. Nenhuma diferença foi observada dentro de métodos de pastejo (P = 0,5128), comprovando que, em pastagem de azevém, os dois métodos se equivaleram em produção de carne por unidade de área.…”
Section: Ep = Erro-padrão (Se = Standard Error)unclassified
“…Pesquisadores (Orr et al, 1990;Penning et al, 1991;Armstrong, 1995) verificaram que as maiores produções por área ocorreram em menores alturas da pastagem, porém com reduzido desempenho animal. Nenhuma diferença foi observada dentro de métodos de pastejo (P = 0,5128), comprovando que, em pastagem de azevém, os dois métodos se equivaleram em produção de carne por unidade de área.…”
Section: Ep = Erro-padrão (Se = Standard Error)unclassified
“…Consequently, in swards continuously grazed by cattle, such areas may buffer decline in clover content and maintain reasonably constant annual levels or impose only gradual decline from very high levels. In contrast to cattle-grazed swards, reduction in white clover content in sheep grazed swards can be rapid under continuous grazing (Orr et al, 1990). This is partly accounted for by rapid branching in the early stages of sheep grazing.…”
Section: Grazing Effectsmentioning
confidence: 94%
“…Comparisons are variable, however. Sheep production from grass/clover swards has been less than 75% that of grass swards receiving 400 kg N ha -1 (Orr et al, 1990).…”
Section: Animal Productionmentioning
confidence: 99%
“…Several studies have shown that herbage intake by sheep grazing in temperate pastures is severely depressed when sward height falls under 4 cm (Allden and Whittaker, 1970;Penning, 1986;Orr et al, 1990). One of the main arguments that could be used to explain reduced intake where there is a low sward height is that the amount that can be taken with each bite is low (Stobbs, 1973;Penning, 1986;Orr et al, 1990). In a mechanistic explanation of reduced intake on short swards, the lower weight of each bite can partly be offset by the animal increasing the number of harvesting bites.…”
Section: Discussionmentioning
confidence: 99%